PENGARUH MOTIVASI, KEPUASAN KERJA, DALAM PENYUSUNAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH ( Studi Pada Pemerintahan Kabupaten Batang Hari ) - Etty Siswati (Universitas Batanghari Jambi, 2014)
The purpose of this research is (1) To find out the influence of motivation in the development of budget to the performance of Batang Hari Regency Government, 2. To find out the influence of job satisfaction in the development of budget to the performance Batang Hari Regency Government . Data collection method used this survey method is used to get information from respondents by using techniques of interview and spread a list of questions and using the measurement likert scale. Population in this research is includes the whole head SKPD has the data, the number of 104 random sampling stratifikasi allocation with 2 respondents every strata, in this case SKPD has as strata. The appliance data analysis is used multiple regression method using this computer assistance program through SPSS 20.0 for windows.The results of the analysis shows the motivation,influential positive and significant impact to the performance local government forces, and job satisfaction has positive effect and singnifikan to the performance of the employees of local government.Key Words : motivation, job satisfaction, performance and Local Government of Batang Hari.